Study of Extraction of Silver(I) in Nitric Acid Media by 2-Ethylhexyl Octyl Sulfide - Li, Jinfei; Liu, Yan; Huang, Zhangjie (Asian Journal of Chemistry, 2015)
Extraction performance of Ag(I) was studied using 2-ethylhexyl octyl sulfide as extractant from nitric acid media. Ag(I) transferring was depended on the 2-ethylhexyl octyl sulfide and nitric acid concentration, phase ratio (O/A), contact time and Ag(I) concentration in stock solution. By controlling 2-ethylhexyl octyl sulfide and nitric acid concentration, Ag(I) could be separated effectively from mixing solution containing Pt(IV), Rh(III), Fe(III), Cu(II), Co(II), Zn(II) and Ni(II) impurities when 2-ethylhexyl octyl sulfide and nitrate acid concentration were fixed at 6 % (v/v) and 4 M, respectively. Silver(I) loaded in organic phase was stripped effectively with thiourea solution.